Analysis of COVID-19 pandemic in USA, using Topological Weighted Centroid. (September 2021) - Asadi-Zeydabadi, Masoud; Buscema, Massimo; Lodwick, Weldon; Massini, Giulia; Della Torre, Francesca; Newman, Francis
Abstract: The first case of COVID-19 in USA was reported on January 20, 2020. The number of COVID-19 confirmed cases and death has increased since the first reported case and the outbreak has appeared in all states. This paper analyzes disease outbreak using Topological Weighted Centroid (TWC), which is a data driven intelligent geographical dynamical system that models disease spread in space and time. In this analysis the COVID-19 cases in USA on March 26, 2020 as provided by Johns Hopkins University is used. The COVID-19 outbreak is mapped by the TWC method. We were able to predict and capture some features of the pandemic spread using the early data. Although we have used the geographical distance from the latitude and longitude coordinates, our results indicate that one of the main paths of diseases spread are arguably airline routes. In this analysis, we used a large set of data. A modified version of TWC, is named TWC-Windowing to elaborate the effect of data from all places. Highlights: In this analysis, Topological Weighted Centroid (TWC) is used. TWC is a data driven geographic dynamic model that consists of 5 sets of algorithms. TWC-Windowing, which is a new type of TWC method for the first time is used in this paper. TWC method is developed based on the concept of statistical thermodynamic. In this analysis the COVID-19 cases in USA on March 26, 2020 as provided by Johns Hopkins University is used. According to the TWC results, it is hypothesized that the main routes of COVID-19 spread are the airline connection.